Inovação tecnológica, aprendizado vivencial e direito: a experiência concreta como fonte de conhecimento para o preparo do jurista brasileiro no século XXI - Costa, Camile Souza (Universidade do Vale do Rio dos Sinos, 2024)
By indicating concrete experience as the source of knowledge for the preparation of Brazilian jurists in fulfilling their important role in a society undergoing transformation, the proposed objective is to address the act of knowing in its essence and authenticity as an important tool to tackle the challenges caused by technological advancements, especially the widespread use of artificial intelligence in the early decades of the 21st century. The focus is on young law students, members of Generation Z, based on Luciano Floridi's conception, as they possess the potential to bring about the necessary changes in a reality where online and offline are no longer distinguishable, and information - or data - is the new generative power of reality. In this context, theoretical learning, while indispensable, needs to be accompanied by concrete experience, i.e., experiential learning, so that responses to the mentioned challenges are consistently aligned with immediate reality and provide ethical and responsible solutions. The proposed method to achieve this is the problematization methodology, and thus, the problem of this research is to identify: to what extent this methodology encourages students to connect with reality for their self-improvement, towards identifying the most functional legal response to each presented context? As for the methodology, a literature review and the analysis of environments where learning occurs through contextualized experience are employed. The conclusion is that in an unprecedented reality with still unknown challenges, theory proves to be a valid instrument when complemented by on-site experience, i.e., the perception gained from direct immersion in the context where the issue to be resolved arises. Thus, knowledge arises from the concrete, from reality as it manifests, and the future legal professional, the current law student, by internalizing it, is then able to learn, from their own experiences, to find answers that balance innovation, ethics, and responsibility—essential qualities jointly needed for the 21st century.
Keywords: Inovação tecnológica; Aprendizado; Experiência; Direito; Inteligência artificial; Metodologia da problematização; Technological innovation; Learning; Experience; Law; Artificial intelligence; Problem-based methodology; ACCNPQ::Ciências Sociais Aplicadas::Direito